Separator and lithium secondary battery including said separator
By coating inorganic particles and polymer adhesive on the polypropylene-based separator to form a local aggregation coating, the problem of lithium-ion batteries melting at high temperatures is solved, the thermal stability and assembly operability of the batteries are improved, and safety risks are reduced.
Patent Information
- Application Number
- JP2024543251
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-26
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-01-26
AI Technical Summary
The separators of existing lithium-ion batteries are prone to melt at high temperatures and cause safety hazards, and the polyvinyl separators prepared by wet method are insufficient in lithium-ion batteries for electric vehicles, resulting in increased safety risks.
The polypropylene-based separator prepared by dry method is coated with inorganic particles and polymer adhesive on its surface to form a coating with local aggregation, which improves the surface roughness and viscosity of the separator and improves the operability of the battery assembly process.
It improves the thermal stability of lithium-ion batteries and the operability of the battery assembly process, reduces the risk of battery short circuit, and improves the safety performance of the battery.
Smart Images

Figure 2025504489000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator and a lithium secondary battery including the separator.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0011705 filed on January 26, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Recently, interest in energy storage technology has been increasing. As the fields of application expand to include energy for mobile phones, camcorders, and laptops, as well as electric vehicles, efforts in research and development of electrochemical elements are gradually becoming more concrete. Among these, interest is being shown in the development of secondary batteries, which are energy storage devices that can be charged and discharged based on electrochemical principles. In addition, in the development of such batteries, research and development related to new electrode and battery designs has been conducted recently in order to improve the capacity density and specific energy.
[0004] There is an increasing demand for higher energy density batteries used as power sources for such electronic devices. Lithium secondary batteries are the batteries that can best meet such demands, and research into them is currently being actively conducted.
[0005] Lithium-ion secondary batteries, in particular, are batteries that can be used repeatedly because lithium ions store and generate electricity by going back and forth between positive and negative electrodes. Lithium-ion secondary batteries are characterized by high voltage and energy density, long cycle life, excellent storage properties, and high output, and are therefore being applied in a wide range of fields, including portable IT devices, batteries for electric vehicles, and energy storage systems (ESS). Among these, the spread of electric vehicles is the main key to the growth of secondary batteries and is the main growth driver of the secondary battery market.
[0006] The four main components of such a secondary battery are a positive electrode, a negative electrode, an electrolyte, and a separator. Among these, the separator separates the two electrodes in the secondary battery, the positive electrode and the negative electrode, to prevent electrical shorting caused by physical contact, and provides a path through which ions can move between the two electrodes via the electrolyte held in the micropores, thereby providing ion conductivity.
[0007] Such separation membranes are made of microporous polymer film materials having the above-mentioned functions, and polyolefin-based separation membranes are particularly widely used. Representative polyolefin-based separation membranes include polyethylene (PE)-based and polypropylene (PP)-based polymer materials.
[0008] The manufacturing methods for forming such a microporous structure are broadly divided into a dry process based on a stretching process and a wet process based on an extraction process, and dry and wet separators are used depending on the desired characteristics. Research and development of both of these two methods is ongoing, but currently wet separators dominate the secondary battery separator market.
[0009] Specifically, wet separation membranes using polyethylene (PE) polymers, a representative polyolefin-based separation membrane, have been used without major problems in small lithium-ion secondary batteries for portable electronic devices. However, when used in electric vehicles or when the battery is misused, problems have been raised in recent years regarding poor heat resistance, such as a meltdown phenomenon occurring when the battery temperature rises above the melting point of PE due to its low melting point (Tm), which can cause fires and explosions.
[0010] To solve this problem, dry separators using polypropylene (PP)-based polymers with excellent thermal properties are being used in earnest, and a technology has been developed to coat the surface of the separator with inorganic particles and a polymer binder to ensure the stability of lithium-ion batteries when using polypropylene (PP)-based polymers. The ceramic-coated safety reinforced separator (SRS), developed as part of this, has been applied to lithium-ion secondary batteries for electric vehicles and has become the standard for heat-resistant separator technology. To manufacture such separators, wet separators, which are easy to make thin, are mainly used.
[0011] As a method for manufacturing such a wet separator, a method of coating a polymer binder on a dry PP film using an immersion phase separation method, which is a nonsolvent induced phase separation method (NIPS), has been researched and developed. This method has the advantage of reducing process costs by reusing the solvent, such as N-methyl-2-pyrrolidone (NMP), and ensuring uniform coating and adhesive strength, but has the disadvantage of being difficult to operate due to the viscosity of the coating layer during the battery assembly process. Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a separator for a lithium secondary battery that has excellent electrochemical performance and ensures stability.
[0013] Another object of the present invention is to provide a separator having improved viscosity of a coating layer in the separator, thereby improving workability in an assembly process during battery manufacturing.
[0014] Another object of the present invention is to provide a separator having improved viscosity of a coating layer as well as increased surface roughness, thereby improving workability in an assembly process during battery manufacturing.
[0015] Another object of the present invention is to provide a method for producing a separator having the above-mentioned properties and a lithium secondary battery using the separator. [Means for solving the problem]
[0016] In order to solve the above problems, According to one aspect of the present invention, there is provided a separation membrane according to the following embodiment.
[0017] According to the first embodiment, A separation membrane is provided, which comprises a polymeric porous support and a coating layer located on at least one surface of the polymeric porous support and containing a binder polymer, the binder polymer comprising a polyvinylidene fluoride-based polymer and a cyanoethylated polymer, and the coating layer has a surface roughness (Ra) of 300 nm to 500 nm.
[0018] According to the second embodiment, in the first embodiment, The cyanoethylated polymer may include cyanoethyl polyvinyl alcohol, cyanoethyl pullulan, cyanoethyl cellulose, cyanoethyl sucrose, cyanoethyl ester, cyanoethyl acetate, cyanoethyl phosphate, or a mixture of two or more thereof.
[0019] According to the third embodiment, in the first or second embodiment, The cyanoethyl polyvinyl alcohol may contain a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2 in a molar ratio of 50:50 to 70:30.
[0020] [ka]
[0021] [ka]
[0022] According to the fourth embodiment, in any one of the first to third embodiments, The cyanoethylated polymer may have a weight average molecular weight (Mw) of 100,000 g / mol to 400,000 g / mol, a number average molecular weight (Mn) of 50,000 g / mol to 200,000 g / mol, and a glass transition temperature (Tg) of 0°C to 100°C.
[0023] According to the fifth embodiment, in any one of the first to fourth embodiments, The polyvinylidene fluoride polymer may include one or more selected from polyvinylidene fluoride, polyvinylidene fluoride-tetrafluoroethylene (PVDF-TFE), polyvinylidene fluoride-chlorotrifluoroethylene, polyvinylidene fluoride-trifluoroethylene, and polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene.
[0024] According to the sixth embodiment, in any one of the first to fifth embodiments, The polyvinylidene fluoride polymer may include polyvinylidene fluoride-chlorotrifluoroethylene.
[0025] According to the seventh embodiment, in any one of the first to sixth embodiments, The weight ratio of the polyvinylidene fluoride polymer to the cyanoethylated polymer may be 85:15 to 99:1.
[0026] According to the eighth embodiment, in any one of the first to seventh embodiments, The coating layer may be formed by localized aggregation on the surface of the polymeric porous support.
[0027] According to the ninth embodiment, in any one of the first to eighth embodiments, The coating layer may have a surface roughness (Ra) of 320 nm to 420 nm.
[0028] According to another aspect of the present invention, there is provided a method for producing a separator according to the following embodiment.
[0029] According to the tenth embodiment, The present invention provides a method for producing a separation membrane, comprising the steps of: applying a coating slurry containing a binder polymer to at least one surface of a polymeric porous support; and immersing the polymeric porous support to which the coating slurry has been applied in a composition containing a non-solvent for the binder polymer to form a coating layer, wherein the binder polymer comprises a polyvinylidene fluoride-based polymer and a cyanoethylated polymer, and the coating layer has a surface roughness (Ra) of 300 nm to 500 nm.
[0030] According to the eleventh embodiment, in the tenth embodiment, The coating slurry may have a solid content of 1% to 7% by weight.
[0031] According to yet another aspect of the present invention, there is provided a lithium secondary battery according to the following embodiment.
[0032] According to the twelfth embodiment, There is provided a lithium secondary battery including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being any one of the first to ninth embodiments described above.
[0033] According to the thirteenth embodiment, A method for manufacturing a separator according to any one of the first to ninth embodiments described above is provided.
[0034] According to the fourteenth embodiment, There is provided a lithium secondary battery including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being manufactured by the method for manufacturing a separator according to any one of the tenth, eleventh, and thirteenth embodiments. Effect of the Invention
[0035] The separator according to one embodiment of the present invention has excellent ion conductivity and prevents electrical short circuit between a positive electrode and a negative electrode, and when used in a secondary battery, can improve the heat resistance stability of the battery.
[0036] In the separator according to an embodiment of the present invention, the surface viscosity is improved due to localized cohesion of the coating layer, which can improve the workability during the battery assembly process and the performance of the manufactured battery.
[0037] According to one aspect of the present invention, the separator induces instability of phase separation during manufacture and induces aggregation of the coating layer, thereby improving surface roughness, thereby improving workability during the battery assembly process and the performance of the manufactured battery.
[0038] The method for producing a separation membrane according to one aspect of the present invention can produce the above-mentioned separation membrane.
[0039] According to one aspect of the present invention, a method for producing a separation membrane can produce a coating layer that is locally coagulated within the separation membrane by using a coating slurry having a low solid content, thereby producing a separation membrane with improved viscosity.
[0040] The lithium secondary battery according to an embodiment of the present invention can improve heat resistance stability and battery performance by using the separator as described above.
[0041] The characteristics of the separator, the method for manufacturing the separator, and the lithium secondary battery according to one embodiment of the present invention are not limited to those described above, and the effects of the present invention are not limited to those described above.
[0042] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]
[0043] [Figure 1] 1 is a SEM image of a coating layer according to Example 1 of the present invention. [Diagram 2] 1 is a SEM image of a coating layer according to Example 2 of the present invention. [Diagram 3] 2 is a SEM image of a coating layer according to Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] The present invention will be described in detail below. However, the present invention is not limited to the following content, and each component may be modified or mixed in various ways as necessary. Therefore, it should be understood that the present invention includes all modifications, equivalents, and alternatives included in the spirit and technical scope of the present invention.
[0045] The "weight average molecular weight (Mw)" and "number average molecular weight (Mn)" used in this specification are measured by conventional methods well known in the art, and may be measured, for example, by gel permeation chromatography (GPC).
[0046] As used herein, the "glass transition temperature (Tg)" is measured by a conventional method well known in the art, and may be measured, for example, by Differential Scanning Calorimetry (DSC).
[0047] The term "surface roughness (Ra)" used in this specification refers to the average height of the curve formed by the cut surface of the surface, measured assuming that the surface is flat and free of roughness over a reference length (center mean line), and may be measured using, for example, an optical profiler (New View 8300, manufactured by Zygo).
[0048] As used herein, "pore size" is measured by conventional methods well known in the art, and may be measured, for example, by capillary flow porometry.
[0049] As used herein, "porosity%" refers to a value obtained by subtracting the volume calculated from the thickness, width, and length of the layer to be measured for porosity from the volume calculated based on the weight and density of each component of the layer to be measured.
[0050] As used herein, the term "average particle size (D 50 "D" refers to the particle diameter at 50% of the cumulative particle number distribution according to the particle diameter, and the particle diameter may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and when the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. The particle diameter at the 50% point of the cumulative particle number distribution according to the particle diameter is calculated in the measuring device, whereby D 50 The particle size may be measured.
[0051] The separation membrane according to one embodiment of the present invention comprises: The present invention comprises a polymeric porous support and a coating layer located on at least one surface of the polymeric porous support and containing a binder polymer, the binder polymer containing a polyvinylidene fluoride-based polymer and a cyanoethylated polymer, and the surface roughness (Ra) of the coating layer is 300 nm to 500 nm.
[0052] According to an embodiment of the present invention, the polymeric porous support is not limited as long as it has a structure having pores, and may be a porous polymer substrate, specifically, at least one of a porous polymer film substrate and a porous polymer nonwoven fabric substrate.
[0053] The porous polymer film substrate may be, but is not limited to, a porous polymer film containing polyolefin such as polyethylene (PE) or polypropylene (PP). The porous polymer film substrate made of polyolefin may exhibit a shutdown function at a temperature of, for example, 80°C to 130°C.
[0054] In this case, the polyolefin may include polyethylene such as high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ultra-high molecular weight polyethylene (UHMWPE); polypropylene; polybutylene; polypentene; polyhexene; polyoctene; a copolymer of two or more of ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene; or a mixture thereof.
[0055] Representative examples of commercially available polyolefin porous polymer films that can be used as such polymeric porous supports include, but are not limited to, wet polyethylene systems (Asahi Kasei E-Materials, Toray, SK I.E. Technology, Shanghai Energy, Sinoma, Entek), dry polypropylene systems (Shenzhen Senior, Cangzhou Mingzhu), and dry polypropylene / polyethylene multilayer structures (Polypore, Ube).
[0056] The weight average molecular weight (Mw) of the polyolefin may be 200,000 g / mol to 1,500,000 g / mol, 220,000 g / mol to 1,000,000 g / mol, or 250,000 g / mol to 800,000 g / mol. When the weight average molecular weight of the polyolefin is within the above range, the uniformity and membrane forming processability of the porous support to which the polyolefin is applied are ensured, and a separation membrane having excellent final strength and heat resistance is obtained.
[0057] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester in addition to polyolefin into a film shape. In addition, the porous polymer film substrate may be formed in a structure in which two or more film layers are laminated, and each film layer may be formed from the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.
[0058] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, etc., either alone or in combination, in addition to the above-mentioned polyolefins.
[0059] The thickness of the polymeric porous support is not particularly limited, and may be 1 μm or more, 5 μm or more, 50 μm or less, or 100 μm or less. When the thickness of the polymeric porous support satisfies this range, the problem of acting as a resistance layer can be improved while maintaining mechanical properties, but the present invention is not limited thereto.
[0060] The pore size and porosity of the polymeric porous support are not particularly limited, but the porosity may be in the range of 10 to 95%, and the pore size (diameter) may be in the range of 0.1 μm to 50 μm. When the pore size and porosity are in such ranges, the problem of acting as a resistance layer can be prevented and mechanical properties can be maintained. In addition, the polymeric porous support may be in the form of a fiber or membrane.
[0061] According to an embodiment of the present invention, the coating layer located on at least one surface of the polymeric porous support includes a binder polymer, and the binder polymer includes a polyvinylidene fluoride-based polymer and a cyanoethyl polyvinyl alcohol.
[0062] Polyvinylidene fluoride (PVDF) is a material that is widely used in microfiltration (MF) membranes and ultrafiltration (UF) membranes that are mainly used in water treatment because of its high thermal stability and chemical resistance, and is also a material that has been intensively studied in the manufacture of separation membranes. Specifically, PVDF is a crystalline polymer that is composed of 59.4% fluorine, 3% hydrogen, and the remaining 37.6% carbon atoms, and is divided into four types of structures, α, β, γ, and δ, depending on its crystal structure, and these structures are replaced depending on certain conditions such as temperature, cooling rate, and stretching. PVDF usually has a crystallinity of 35% to 70%, but the crystal structure and crystallinity can have a significant effect on the mechanical properties of PVDF. In addition, PVDF has high heat resistance due to strong C-F bonds, and has relatively stable chemical resistance except for basic solutions, esters, ketones, etc. For this reason, when PVDF is used, there are more options for solvents than conventional polymer materials such as PP and PTFE, and it is possible to easily manufacture separators with various pore structures by the phase inversion method.
[0063] Accordingly, the binder polymer includes a polyvinylidene fluoride (PVDF)-based polymer, which has an advantage of providing a stable separator, but the characteristics of the present invention are not limited thereto.
[0064] As used herein, the term "polyvinylidene fluoride polymer" refers to a polymer having a -(C 2 H 2 F 2 )-repeating units in the polymer structure, 2 H 2 F 2 It is used to collectively refer to all polymers that contain at least one repeating unit represented by the formula:
[0065] The polyvinylidene fluoride polymer may include, for example, one or more selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-tetrafluoroethylene (PVDF-TFE), polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE), and polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene (PVDF-TrFE-CFE), but is not limited thereto.
[0066] In one embodiment of the present invention, the polyvinylidene fluoride-based polymer may include polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE).
[0067] In another embodiment of the present invention, the polyvinylidene fluoride-based polymer may have a glass transition temperature (Tg) of, for example, −200° C. to 200° C. When the glass transition temperature of the binder polymer satisfies the above range, the mechanical properties such as flexibility and elasticity of the finally formed coating layer may be improved, but the present invention is not limited thereto.
[0068] In yet another embodiment of the present invention, the polyvinylidene fluoride polymer may have ion conductivity. By including an ion-conductive binder polymer, the performance of the battery can be further improved. The polyvinylidene fluoride polymer may have a dielectric constant of 1.0 to 100 (measurement frequency = 1 kHz), or 10 to 100. When the dielectric constant satisfies the above-mentioned range, there is an effect of improving the dissociation degree of salt in the electrolyte, but the present invention is not limited thereto.
[0069] As used herein, the term "cyanoethylated polymer" refers to a polymer that has a cyanoethyl group (-C) at at least one position within its structure. 2 H 4 It is used as a general term for all polymers in which the aryl group is substituted with CN.
[0070] For example, in one embodiment of the present invention, the cyanoethylated polymer may be cyanoethyl polyvinyl alcohol, and the term "cyanoethyl polyvinyl alcohol" refers to a polyvinyl alcohol having at least one hydroxyl group (-OH) that is substituted with a cyanoethyl group (-C 2 H 4 The cyanoethyl polyvinyl alcohol refers to a polyvinyl alcohol that is cyanoethylated by substitution with hydroxyl group (CN). The cyanoethyl polyvinyl alcohol may be used without any limitation as long as it has a structure in which at least one hydroxyl group of polyvinyl alcohol is cyanoethylated, and the method for producing the same is not particularly limited.
[0071] The binder polymer contains a cyanoethylated polymer, so that the non-solvent water (H 2 O) increases the affinity for the polymer, inducing instability in phase separation, thereby inducing the formation of a locally aggregated coating layer, but the mechanism of the present invention is not limited thereto.
[0072] According to other embodiments of the present invention, the cyanoethylated polymer may include, but is not limited to, for example, cyanoethyl polyvinyl alcohol, cyanoethyl pullulan, cyanoethyl cellulose, cyanoethyl sucrose, cyanoethyl ester, cyanoethyl acetate, cyanoethyl phosphate, or a mixture of two or more thereof.
[0073] In one embodiment of the invention, the cyanoethylated polymer may include cyanoethyl polyvinyl alcohol.
[0074] In one embodiment of the present invention, the cyanoethyl polyvinyl alcohol may consist only of a repeating unit represented by the following Chemical Formula 1:
[0075] [ka]
[0076] In one embodiment of the present invention, the cyanoethyl polyvinyl alcohol may contain a repeating unit represented by the following Chemical Formula 2 in addition to the repeating unit represented by Chemical Formula 1, provided that the cyanoethyl polyvinyl alcohol is not 100% cyanoethylated with respect to the hydroxyl groups of the polyvinyl alcohol.
[0077] [ka]
[0078] In one embodiment of the present invention, the cyanoethyl polyvinyl alcohol may include a repeating unit represented by Chemical Formula 1 and a repeating unit represented by Chemical Formula 2, and for example, the molar ratio of the repeating unit represented by Chemical Formula 1 to the repeating unit represented by Chemical Formula 2 may be, but is not limited to, 50:50 to 70:30.
[0079] In another embodiment of the present invention, the molar ratio of the repeating unit represented by Chemical Formula 1 to the repeating unit represented by Chemical Formula 2 may be, for example, 50:50 or more, 55:45 or more, 60:40 or more, 62.5:37.5 or more, 70:30 or less, or 67.5:32.5 or less. When the molar ratio between the repeating units is within the above range, an effect of improving the viscosity of the coating layer is achieved, but the present invention is not limited thereto.
[0080] In another embodiment of the present invention, the cyanoethylated polymer may have a weight average molecular weight (Mw) of 100,000 g / mol to 400,000 g / mol. Specifically, the Mw of the cyanoethylated polymer may be 100,000 g / mol to 350,000 g / mol, more specifically, 130,000 g / mol to 300,000 g / mol, or 150,000 g / mol to 250,000 g / mol.
[0081] In another embodiment of the present invention, the cyanoethylated polymer may have a number average molecular weight (Mn) of 50,000 g / mol to 200,000 g / mol. Specifically, the Mn of the cyanoethylated polymer may be 80,000 g / mol to 170,000 g / mol, or 100,000 g / mol to 140,000 g / mol.
[0082] In another embodiment of the present invention, the cyanoethylated polymer may have a glass transition temperature (Tg) of 0° C. to 100° C. Specifically, the Tg of the cyanoethylated polymer may be 30° C. to 90° C., 50° C. to 80° C., more specifically, 10° C. to 60° C.
[0083] In another embodiment of the present invention, the cyanoethylated polymer may have a weight average molecular weight (Mw) of 150,000 g / mol to 250,000 g / mol, a number average molecular weight (Mn) of 100,000 g / mol to 140,000 g / mol, and a glass transition temperature (Tg) of 10°C to 60°C.
[0084] In the present invention, when the Mw, Mn and Tg of the cyanoethylated polymer satisfy the above-mentioned ranges, the viscosity of the coating layer can be improved, but the present invention is not limited thereto.
[0085] In one embodiment of the present invention, the weight ratio of the polyvinylidene fluoride polymer to the cyanoethylated polymer in the binder polymer may be, for example, 85:15 to 99:1 (polyvinylidene fluoride polymer: cyanoethylated polymer). Specifically, the weight ratio may be 90:10 to 99:1, 85:15 to 95:5, or 90:10 to 95:5, more specifically, 93:7 to 95:5, or 90:10 to 93:7, and even more specifically, 93:7. When the weight ratio satisfies the above range, the degree of improvement in the viscosity of the coating layer is improved, but the present invention is not limited thereto.
[0086] In the separator according to one embodiment of the present invention, the surface roughness (Ra) of the coating layer is 300 nm to 500 nm. Specifically, it may be 300 nm or more, 310 nm or more, 320 nm or more, 330 nm or more, 340 nm or more, 350 nm or more, 360 nm or more, 370 nm or more, 380 nm or more, 390 nm or more, or 400 nm or more, 500 nm or less, 490 nm or less, 480 nm or less, 470 nm or less, 460 nm or less, or 450 nm or less. More specifically, the surface roughness (Ra) of the coating layer may be 300 nm to 500 nm or 320 mm to 420 mm. When the surface roughness (Ra) of the coating layer satisfies the range of 300 nm to 500 nm, it is advantageous in that a frictional force is generated and the running characteristics are improved.
[0087] In one embodiment of the present invention, the binder polymer may further include a conventional binder polymer in addition to the above-mentioned polyvinylidene fluoride-based polymer and cyanoethylated polymer. Examples of the conventional binder polymer that may be further included include, but are not limited to, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, pullulan, carboxymethyl cellulose, styrene-butadiene copolymer, polyimide, or a mixture of two or more thereof.
[0088] In another embodiment of the present invention, when the binder polymer further includes another binder polymer in addition to the polyvinylidene fluoride-based polymer and the cyanoethylated polymer, the content of the additional binder polymer is sufficient as long as it does not deviate from the object of the present invention, and is not particularly limited.
[0089] In one embodiment of the present invention, the coating layer may have a thickness of 1.5 μm to 5.0 μm on one side of the polymeric porous support. When the coating layer has a thickness in the above range, the fixed running property is improved due to the generation of surface friction, and the cell strength of the battery can be easily increased while the adhesion to the electrode is excellent.
[0090] According to an embodiment of the present invention, the coating layer may be formed by localized aggregation on the surface of the polymeric porous support.
[0091] The coating layer may be formed by inducing instability of phase separation by minimizing the solid content of a slurry composition for preparing the coating layer, which includes a polyvinylidene fluoride-based polymer and cyanoethyl polyvinyl alcohol as binder polymers, thereby forming a locally aggregated coating layer on at least one surface of the polymeric porous support.
[0092] In one embodiment of the present invention, the state in which the coating layer is formed by localized aggregation can be observed, for example, with a scanning electron microscope (SEM).
[0093] In another embodiment of the present invention, whether the coating layer is formed in a locally aggregated state may be confirmed, for example, by measuring the surface roughness (Ra) of the coating layer.
[0094] The separator according to one embodiment of the present invention may improve the viscosity of the coating layer and increase the surface roughness, thereby improving the ease of assembly of the battery, but the properties of the separator according to the present invention are not limited thereto.
[0095] According to another embodiment of the present invention, a method for producing a separator includes: The method for manufacturing a separation membrane includes the steps of: applying a coating slurry containing a binder polymer to at least one surface of a polymeric porous support; and immersing the polymeric porous support coated with the coating slurry in a composition containing a non-solvent for the binder polymer to form a coating layer, wherein the binder polymer includes a polyvinylidene fluoride-based polymer and a cyanoethylated polymer, and the coating layer has a surface roughness (Ra) of 300 nm to 500 nm.
[0096] In the method for producing a separation membrane according to one embodiment of the present invention, the polymeric porous support, the binder polymer, the polyvinylidene fluoride-based polymer, the cyanoethylated polymer, the configuration of the coating layer, and the surface roughness (Ra) of the coating layer are the same as those described above for the separation membrane.
[0097] In an embodiment of the present invention, the forming of the coating layer may include forming a coating layer on at least one surface of the polymeric porous support by immersion phase separation using a coating slurry including a binder polymer.
[0098] Specifically, the step of forming the coating layer may include the steps of: applying a coating slurry containing a binder polymer and a solvent to at least one surface of the polymeric porous support; and immersing the polymeric porous support to which the coating slurry has been applied, into a composition containing a non-solvent for the binder polymer to form the coating layer.
[0099] The solvent may have a solubility index similar to that of the binder polymer and a low boiling point, which facilitates uniform mixing and subsequent solvent removal.
[0100] Examples of such solvents may be one or more compounds selected from the group consisting of acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, methanol, ethanol, isopropyl alcohol, and water, each of which may be independently selected.
[0101] In this case, the solvent may function as a solvent for dissolving the binder polymer or as a dispersion medium for dispersing the binder polymer, depending on the type of the binder polymer to be mixed.
[0102] According to an embodiment of the present invention, the method of applying the coating slurry to the polymeric porous support includes a pre-metering method and a post-metering method. The pre-metering method is a method in which a coating amount is determined in advance and introduced, such as slot die coating and gravure coating. The post-metering method is a method in which a sufficient amount of the coating solution, the slurry, is applied to the polymeric porous support, and then a specified amount is scraped off, such as bar coating. There is also a direct-metering coating method that combines the pre-metering method and the post-metering method.
[0103] The coating slurry may be applied by any of the non-limiting methods described above, and the polymeric porous support to which the coating slurry has been applied may be immersed in a composition containing a non-solvent to cause phase separation and form a coating layer.
[0104] In one embodiment of the present invention, the solid content in the coating slurry may be 1 wt% to 7 wt%. Specifically, the solid content may be 1 wt% or more, 1.5 wt% or more, 2 wt% or more, 2.5 wt% or more, or 3 wt% or more, 7 wt% or less, 6.5 wt% or less, 6 wt% or less, 5.5 wt% or less, 5 wt% or less, 4.5 wt% or less, or 4 wt% or less, for example, 1 wt% to 7 wt%, 2 wt% to 6 wt%, or 3 wt% to 6 wt%. When the solid content in the coating slurry is within the above range, a non-uniform coating layer is formed on the polymeric porous support, and the viscosity problem of the coating layer can be improved. For example, when the solid content is less than 1 wt%, no clumping of the coating layer occurs and the change in Ra is not large. In addition, when the solid content exceeds 7 wt%, there is a problem that the improvement in effect is insufficient compared to the input cost of the solid content.
[0105] In another embodiment of the present invention, the solid content in the coating slurry is set to 7 wt % or less, thereby inducing instability in phase separation during immersion phase separation of the coating layer, thereby producing a coating layer in which localized aggregation of the coating layer is induced, but the mechanism of the present invention is not limited thereto.
[0106] According to a method for producing a separation membrane according to an embodiment of the present invention, the above-mentioned separation membrane can be produced.
[0107] According to another embodiment of the present invention, there is provided a lithium secondary battery comprising: The battery includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and the separator includes the above-mentioned separator.
[0108] A lithium secondary battery including a separator according to an embodiment of the present invention uses a separator in which a coating layer having improved surface roughness is formed by localized aggregation on a polymer porous support, and therefore the battery has excellent electrochemical performance and can improve process operability.
[0109] The lithium secondary battery may include a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0110] The positive and negative electrodes to be used with the separator of the present invention are not particularly limited, and may be prepared by bonding an electrode active material to an electrode current collector by a conventional method well known in the art.
[0111] Non-limiting examples of the positive electrode active material among the electrode active materials include conventional positive electrode active materials used in the positive electrodes of conventional electrochemical devices, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide combining these may be used.
[0112] Non-limiting examples of the negative electrode active material among the electrode active materials include conventional negative electrode active materials used in the negative electrodes of conventional electrochemical devices, and in particular, lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, or other carbons, silicon, silicon oxide, and other lithium adsorbent materials are preferred.
[0113] Among the electrode current collectors, non-limiting examples of the positive electrode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the negative electrode current collector include foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.
[0114] The electrolyte used in the electrochemical element according to one embodiment of the present invention is + B - A salt with the structure: + Li + , Na + , K + or a combination thereof, - PF 6 -, B.F. 4 - , Cl - , Br - , I - , ClO 4 - , AsF 6 - , C.H. 3 CO 2 - , C.F. 3 SO 3 - , N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof.
[0115] The electrolyte may be injected at an appropriate stage in the battery manufacturing process depending on the manufacturing process and desired physical properties of the final product, i.e., before battery assembly or at the final stage of battery assembly. EXAMPLES
[0116] The present invention will be described in more detail below with reference to examples. Note that the following examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.
[0117] [Separation membrane manufacturing method and evaluation of surface roughness] A separator having a coating layer formed on one side of a dry substrate was obtained by the following method, and the surface roughness (Ra) of the coating layer of the separator was measured using an optical profiler (New View 8300, manufactured by Zygo).
[0118] In producing the coating layer, N-methyl-2-pyrrolidone (NMP) was used as the solvent, and the immersion phase separation was performed by controlling the temperature of the coagulation liquid to less than 20°C, the temperature of the rinsing liquid to more than 40°C, and finally controlling the temperature of the rinsing liquid to a temperature lower than the drying temperature.
[0119] <Example 1> PVDF-CTFE and cyanoethylated PVA binder (CN substitution rate 65 mol%) were mixed in a weight ratio of 93:7 to prepare a slurry with a solid content of 5.5%, and then the slurry was used for dip phase separation coating on a dry substrate (13.6 μm, PP material) using a dot pattern Microgravure bar to prepare a separator with a final thickness of 15 μm.
[0120] The surface roughness (Ra) of the coating layer of the produced separator was 350 nm.
[0121] <Example 2> PVDF-CTFE and cyanoethylated PVA binder (CN substitution rate 65 mol%) were mixed in a weight ratio of 93:7 to prepare a slurry with a solid content of 3%, and a separator with a final thickness of 15 μm was prepared in the same manner as in Example 1, except that a coating layer was formed using the slurry with a lattice-patterned Microgravure bar.
[0122] The surface roughness (Ra) of the coating layer of the produced separator was 450 nm.
[0123] <Comparative Example 1> A separator having a final thickness of 15 μm was prepared in the same manner as in Example 1, except that a slurry having a solid content of 5.5% was prepared using PVDF-CTFE as the binder polymer.
[0124] <Comparative Example 2> A separator having a final thickness of 15 μm was manufactured in the same manner as in Example 1, except that a slurry having a solid content of 1% was prepared by mixing PVDF-CTFE and a cyanoethylated PVA binder (CN substitution rate 87 mol%) in a weight ratio of 95:5, and the coating layer was formed using the slurry.
[0125] The surface roughness (Ra) of the coating layer of the produced separator was 150 nm.
[0126] <Comparative Example 3> A separation membrane having a final thickness of 15 μm was produced in the same manner as in Example 2, except that a cyanoethylated PVA binder with a CN substitution rate of 87 mol % was used.
[0127] The surface roughness (Ra) of the coating layer of the produced separator was 132 nm.
[0128] <Comparative Example 4> A separation membrane having a final thickness of 15 μm was prepared in the same manner as in Example 1, except that a slurry having a solid content of 1% was prepared.
[0129] The surface roughness (Ra) of the coating layer of the produced separator was 152 nm.
[0130] <Comparative Example 5> A separator having a final thickness of 15 μm was manufactured in the same manner as in Example 1, except that a slurry having a solid content of 5.5% was prepared by mixing PVDF-CTFE and PEG400 in a weight ratio of 93:7, and the coating layer was formed using the slurry.
[0131] The surface roughness (Ra) of the coating layer of the produced separator was 164 nm.
[0132] <Comparative Example 6> A slurry with a solid content of 5.5% was prepared by mixing PVDF-CTFE and PEG6000 at a weight ratio of 93:7, and a separation membrane with a final thickness of 15 μm was produced in the same manner as in Example 1, except that the coating layer was formed using this slurry.
[0133] At this time, the surface roughness (Ra) of the coating layer of the produced separation membrane was 144 nm.
[0134] <Analysis results of SEM images> Figure 1 shows the SEM image of the separation membrane of Example 1, Figure 2 shows the SEM image of the separation membrane of Example 2, and Figure 3 shows the SEM image of the separation membrane of Comparative Example 1.
[0135] Comparing the images of Figures 1, 2, and 3, it can be confirmed that the coating layer containing polyvinylidene fluoride-based polymer and cyanoethyl polyvinyl alcohol as the binder polymer has a non-uniform surface and is formed by aggregation in a predetermined region.
[0136] <Analysis results of surface roughness values> From the above results, it was confirmed that the separation membranes according to Examples 1 and 2 have improved surface roughness (Ra), which improves the viscosity of the separation membrane, thereby improving the running stability and workability during the battery assembly process.
[0137] As described above, the present invention has been described with reference to the examples and the drawings. However, the present invention is not limited thereto, and it goes without saying that various applications and modifications within the scope of the present invention are possible by those having ordinary knowledge in the field to which the present invention pertains.
Claims
1. A polymeric porous support; a coating layer located on at least one surface of the polymeric porous support and including a binder polymer; the binder polymer comprises a polyvinylidene fluoride polymer and a cyanoethylated polymer; The coating layer has a surface roughness (Ra) of 300 nm to 500 nm.
2. 2. The separation membrane of claim 1, wherein the cyanoethylated polymer comprises cyanoethyl polyvinyl alcohol, cyanoethyl pullulan, cyanoethyl cellulose, cyanoethyl sucrose, cyanoethyl ester, cyanoethyl acetate, cyanoethyl phosphate, or a mixture of two or more thereof.
3. The separation membrane according to claim 2, wherein the cyanoethyl polyvinyl alcohol contains a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2 in a molar ratio of 50:50 to 70:
30. 【Chemistry 1】 【Chemistry 2】
4. 2. The separation membrane of claim 1, wherein the cyanoethylated polymer has a weight average molecular weight (Mw) of 100,000 g / mol to 400,000 g / mol, a number average molecular weight (Mn) of 50,000 g / mol to 200,000 g / mol, and a glass transition temperature (Tg) of 0° C. to 100° C.
5. The separation membrane according to claim 1, wherein the polyvinylidene fluoride-based polymer comprises one or more selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyvinylidene fluoride-trifluoroethylene, and polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene.
6. The separation membrane according to claim 5 , wherein the polyvinylidene fluoride polymer comprises polyvinylidene fluoride-chlorotrifluoroethylene.
7. 2. The separation membrane according to claim 1, wherein the weight ratio of the polyvinylidene fluoride polymer to the cyanoethylated polymer is from 85:15 to 99:
1.
8. The separation membrane according to claim 1 , wherein the coating layer is formed by localized aggregation on the surface of the polymeric porous support.
9. The separation membrane according to claim 1, wherein the coating layer has a surface roughness (Ra) of 320 nm to 420 nm.
10. Applying a coating slurry containing a binder polymer to at least one surface of a polymeric porous support; and forming a coating layer by immersing the polymeric porous support coated with the coating slurry in a composition including a non-solvent for the binder polymer; the binder polymer comprises a polyvinylidene fluoride polymer and a cyanoethylated polymer; The method for producing a separation membrane, wherein the coating layer has a surface roughness (Ra) of 300 nm to 500 nm.
11. The method for producing a separation membrane according to claim 10, wherein the coating slurry has a solid content of 1 to 7 wt %.
12. The battery includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, A lithium secondary battery, wherein the separator is the separator according to any one of claims 1 to 9.
Citation Information
Patent Citations
Organic / inorganic composite separation membrane coated with a porous active layer and electrochemical element equipped therewith
JP2010517811A
Separator for nonaqueous electrolyte battery, and nonaqueous electrolyte battery
JP2012119224A
Binder for separator of non-aqueous electrolyte battery including 2-cyanoethyl group containing polymer, and separator and battery using the same
JP2012227134A
Binder for separator of non-aqueous electrolyte battery including 2-cyanoethyl group containing polymer, and separator and battery using the same
JP2012227135A
Cyanoethyl group-containing polymer and method for producing same
JP2019509383A